Development and evaluation of a multi-functional organic–inorganic nanotheranostic hybrid for pancreatic cancer therapy. (23rd August 2021) - David, Karolyn Infanta; Ravikumar, T S; Sethuraman, Swaminathan; Krishnan, Uma Maheswari
Abstract: Pancreatic cancer is a highly invasive disease with low survival rates. The high death rates associated with pancreatic cancer are due to multiple factors including late stage diagnosis, multi-drug resistance, invasive nature and restricted access of the therapeutic moiety to the cancer cells due to the stroma. Smart multifunctional nanocarriers that deliver the therapeutic agent in to the cancer tissue as well as enable imaging of the tissue represent an emerging paradigm in cancer therapy. Accurate and reliable detection of cancerous lesions in pancreas is essential for designing appropriate therapeutic strategy to annihilate the highly aggressive pancreatic cancer. A combination of imaging modalities can enhance the reliability of cancer detection. In this context, we report here a hybrid iron oxide-gold nanoparticle with dual contrast enhancing ability for both magnetic resonance imaging (MRI) and micro-computed tomography (micro-CT) that is co-encapsulated with the nucleotide analogue gemcitabine in a chitosan matrix. The theranostic system displayed enhanced cytotoxicity against PanC-1 pancreatic cancer cells when compared to normal cells over 48 h due to differences in cell internalization. The iron oxide-gold hybrid enabled visualization of the theranostic nanoparticle by MRI as well as micro-CT. Further, the magnetocaloric effect of the iron oxide enabled faster release of the chemotherapeutic agent as well as augmented the cytotoxicity by inducing hyperthermia. This system holds promise for further exploration as an integrated diagnostic and therapeutic platform for pancreatic cancer.